2016
DOI: 10.1785/0220150213
|View full text |Cite
|
Sign up to set email alerts
|

A Uniform Database of Teleseismic Shear‐Wave Splitting Measurements for the Western and Central United States: December 2014 Update

Abstract: We present a shear wave splitting (SWS) database for the western and central United States as part of a lasting effort to build a uniform SWS database for the entire North America. The SWS measurements were obtained by minimizing the energy on the transverse component of the PKS, SKKS, and SKS phases. Each of the individual measurements was visually checked to ensure quality. This version of the database contains 16,105 pairs of splitting parameters. The data used to generate the parameters were recorded by 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Only a small fraction of the stations have previously reported SWS measurements, and Long et al [] observed a set of null‐dominated stations in Regions A2 and A3 (Figure ). The mean splitting times for the three regions are 0.91–0.95 s, which are smaller than the global average of 1.0 s and are consistent with those observed on the western part of the stable North American continent using the same procedure [ Yang et al , ]. While the majority of the fast orientations are within 20° from the APM, larger deviations are found in the Great Lakes area.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Only a small fraction of the stations have previously reported SWS measurements, and Long et al [] observed a set of null‐dominated stations in Regions A2 and A3 (Figure ). The mean splitting times for the three regions are 0.91–0.95 s, which are smaller than the global average of 1.0 s and are consistent with those observed on the western part of the stable North American continent using the same procedure [ Yang et al , ]. While the majority of the fast orientations are within 20° from the APM, larger deviations are found in the Great Lakes area.…”
Section: Resultssupporting
confidence: 84%
“…As a nearly ubiquitous characteristic of the Earth's upper mantle, the azimuthal dependence of seismic velocities, i.e., azimuthal anisotropy, has been investigated for decades by numerous studies, mostly using shear wave splitting (SWS) analyses [e.g., Francis , ; Leven et al , ; Mainprice and Nicolas , ; Silver and Chan , ; Gao et al , ; Savage , ; Yang et al , , ]. In particular, splitting of P ‐to‐ S converted phases ( S K S , S K K S , and P K S , hereafter collectively called X K S ) from the core‐mantle boundary is among the most frequently employed structural seismological techniques to determine mantle anisotropy beneath the stations.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Comparison of fast velocity directions (white bars) of P wave azimuthal anisotropy at 75‐km depth determined by this study with the distribution of delay times (colors) of shear wave splitting (SWS) measurements (Barak & Klemperer, ; Ramsay et al, ; Yang et al, ). (b) Comparison of the lithospheric thickness (Lekic et al, ) with P wave azimuthal anisotropy (white bars) at 200‐km depth determined by this study.…”
Section: Resultsmentioning
confidence: 99%
“…We calculate predicted SKS splitting delay time normalΔt and fast direction normalΦ using the above equations, and elastic parameters from model normalUS32. These predictions are compared with station‐averaged SKS splitting measurements from Yang et al (, ) (Figure ). The overall magnitudes of the predicted delay times are smaller than actual measurements, with mean value and standard deviation equaling to 0.64 s and 0.35 s, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the azimuthal anisotropy structures of the North American crust and upper mantle have been explored using a variety of seismic techniques, including shear wave (SKS) splitting (Barruol et al, ; Fouch et al, ; Long et al, ; Savage & Sheehan, ; Wagner et al, ; Yang et al, , ), joint inversion of surface wave waveforms and SKS results (Marone & Romanowicz, ; Yuan & Romanowicz, ; Yuan et al, ), Pn tomography (Buehler & Shearer, ; Smith & Ekström, ), receiver functions (Ford et al, ; Wirth & Long, ), ambient noise tomography (Lin et al, ; Lin & Schmandt, ), and P wave tomography (Huang & Zhao, ).…”
Section: Previous Studies On Azimuthal Anisotropy Of the North Americmentioning
confidence: 99%